Depresi Lanjut Usia - I Ketut Gama; I Gusti Ayu Harini (Jurnal Gema Keperawatan, 2014)
This study aimed to know the description of the level of depression in the elderly based on the with descriptive methods and approaches as well as the cross-sectional survey design to the elderly who were taken in total 35 sampling in village berangbang, jembrana on september 31 to nopember 31, 2013 obtained a sample of 35 respondents. The conclusion that can be drawn up from the results of this study are as follows:Based on age, known to 20 of 35 respondents (57.14%) were observed most respondents aged 70 years.By gender, 19 of the 35 known to respondents (54.29%). studied, most of the respondents are female.Based on the level of education, it is known that 15 of 35 respondents (42.85%). Under study, most respondents did not school. Based on the level of depression was obtained, 14 of 35 respondents (40%) were examined, most of moderate depression.